Course sequencing techniques for large-scale web-based education. (1st January 2003) - Brusilovsky, Peter; Vassileva, Julita
We argue that traditional sequencing technology developed in the field of intelligent tutoring systems could find an immediate place in large-scale web-based education. This paper discusses two models that have been explored by the authors – the dynamic course generation system DCG and the concept-based course maintenance system CoCoA. DCG includes components for domain authoring and for automatic generation of adaptive courses on the WWW. It allows automatic generation of individualised courses according to the learner's goal and previous knowledge, and can dynamically adapt the course according to the learner's success in acquiring knowledge. CoCoA can check the consistency and quality of a course at any moment of its life and also assists course developers in some routine operations.